2010
DOI: 10.1371/journal.ppat.1001188
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Induces DCIR Expression in CD4+ T Cells

Abstract: The C-type lectin receptor DCIR, which has been shown very recently to act as an attachment factor for HIV-1 in dendritic cells, is expressed predominantly on antigen-presenting cells. However, this concept was recently challenged by the discovery that DCIR can also be detected in CD4+ T cells found in the synovial tissue from rheumatoid arthritis (RA) patients. Given that RA and HIV-1 infections share common features such as a chronic inflammatory condition and polyclonal immune hyperactivation status, we hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 60 publications
(71 reference statements)
2
18
0
Order By: Relevance
“…In order to achieve this, we must first increase our understanding of the pathological mechanisms of the disease. Previous studies have shown that the lectin DCIR, expressed primarily on dendritic cells, can bind HIV-1 and participates in cis and trans infection of dendritic cells (Lambert et al, 2008) as well as in trans infection of CD4TL (Lambert et al, 2010). We have also observed previously that infection by HIV-1 increases exosome release from dendritic cells (Subra et al, 2011b).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In order to achieve this, we must first increase our understanding of the pathological mechanisms of the disease. Previous studies have shown that the lectin DCIR, expressed primarily on dendritic cells, can bind HIV-1 and participates in cis and trans infection of dendritic cells (Lambert et al, 2008) as well as in trans infection of CD4TL (Lambert et al, 2010). We have also observed previously that infection by HIV-1 increases exosome release from dendritic cells (Subra et al, 2011b).…”
Section: Discussionsupporting
confidence: 68%
“…It is expressed on the surface of cells of the myeloid lineage, including dendritic cells, neutrophils, monocytes and macrophages, on B lymphocytes (Bates et al, 1999), CD4TL from HIV-1 patients (Lambert et al, 2010) and on CD4 and CD8 T lymphocytes of arthritic patients (Eklow et al, 2008). Previous studies have shown that dendritic cells or apoptotic CD4TL bind HIV-1 via DCIR and that this leads to both trans and cis infection of CD4TL (Lambert et al, 2008(Lambert et al, , 2010. In addition, a series of DCIR inhibitors of small molecular mass have been identified and shown to inhibit HIV-1 interactions with dendritic and CD4TL cells (Lambert et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The DC subsets that may expand in DCIR1-deficient mice have not been characterized. The number of activated CD4 + T cells also increases, consistent with a role for human DCIR in T cell functions during inflammatory and arthritic diseases (109, 110). DCIR1-deficient DCs do not intrinsically possess an enhanced ability to activate T cells, but DCIR1-deficient mice are more susceptible to collagen-induced arthritis, a lymphocyte-dependent model of rheumatoid arthritis induced by immunization with type II collagen/Freund’s complete adjuvant.…”
Section: Pattern-recognition Receptorssupporting
confidence: 62%
“…Human DCIR is predominantly expressed by cells of the myeloid lineage, such as DCs, macrophages, neutrophils, and monocytes [93]. The glycan specificity of human DCIR includes fucose- and mannose-containing glycans, as demonstrated by binding to mannotriose and Lewis b [94].…”
Section: Myeloid C-type Lectins Receptors—pattern Recognition Recementioning
confidence: 99%
“…Human DCIR acts as an attachment factor for HIV-1 on DCs and surface expression of DCIR by CD4 + T cells is induced by HIV-1 [92,93,98,99]. This increased expression of DCIR by CD4 + T cells enhances HIV-1 attachment, viral entry, replication and transfer, finally resulting in a higher virus dissemination [93,99].…”
Section: Myeloid C-type Lectins Receptors—pattern Recognition Recementioning
confidence: 99%